Beta-sitosterol and its antinociceptive mechanism action - Şakul, Ayşe Arzu; Okur, Mehmet Evren (Ankara University, 2022)
Objective: In this study, the possible central antinociceptive activity of beta-sitosterol is investigated along with its association of stimulation of opioidergic, serotonergic, adrenergic, and cholinergic receptors to mice central analgesia because of the beta-sitosterol administration. Material and Method: The beta-sitosterol was administrated to mice in various doses, such as 5, 10 and 20 mg/kg. Then, the mice analyzed via hot-plate and tail-flick assay to investigate the possible antinociceptive effects of beta-sitosterol. Additionally, in order to associate the mechanism of action mechanism, 20 mg/kg of beta-sitosterol was intraperitoneally administered to the animal which were previously pre-treated with opioid antagonist naloxone (5 mg/kg), serotonin 5-HT2A/2C receptor antagonist ketanserin (1 mg/kg), serotonin 5-HT3 receptor antagonist – ondansetron (1 mg/kg), ?2-adrenoceptor antagonist yohimbine (1 mg/kg) and muscarinic antagonist atropine (5 mg/kg), as well as nicotinic antagonist mecamylamine (1 mg/kg). Result and Discussion: The antinociceptive effect of beta-sitosterol was confirmed as dose-dependent for 5, 10, and 20 mg/kg doses in tail-flick and hot-plate tests. It can be concluded that beta-sitosterol promotes central antinociception effects associated with the spinal and supraspinal mediated cholinergic and opioidergic modulation.
Beta-sitosterol ve antinosiseptif etki mekanizması
Keywords: Antinociception; Beta-Sitosterol; Cholinergic Receptors; Opioidergic Receptors